Merawat Kerukunan di Indonesia: Dialog Lintas Agama dan Budaya sebagai Jalan Tengah - Syukron Wahyudhi; Tari Indriani; Resvan; Refor Diansyah; Wulan Purnamasari (CV Global Research Publication, 2026)
The discourse on harmony has always been an interesting topic of discussion. Harmony is inherently a social good, or at least, a desire of many. Indonesia, with a population of about 280 million, is indeed diverse. The six officially recognized religions certainly do not fully represent this diversity. It is well known that many religions and beliefs contribute to the diversity of the Indonesian people. In addition to religion, which is an important element in the identity of its citizens, cultural diversity is also equally important and diverse. This situation requires a common awareness of the importance of maintaining harmony. This study aims to offer new ideas in dealing with this diversity. Using a library research approach, this study presents various perspectives from several figures concerned with the issue of dialogue as the basis for this study to offer new ideas. The results of this study show the need for an open attitude to recognize and be recognized by others, both one's religion and culture, both to and by others. To establish a good dialogue, there must be a willingness to skip and return, as a method of dialogue. Transcending is the courage of every religious believer to abandon their own beliefs, then transcend the beliefs of others, and return to their own beliefs with a new perspective, thus transforming the understanding of the motherland into a wonderland. Similarly, if one can acknowledge that several different cultures can exist in the same environment, then multiculturalism will be created.